FAKTOR-FAKTOR YANG MEMPENGARUHI FIRM PERFORMANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Goewyn, Peggy; Santioso, Linda (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study is to determine the effect of liquidity, leverage, firm size, and institutional ownership on firm performance in manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020. The sampling technique used in this research is purposive sampling method for a total of 72 companies. Data processing in this study was carried out using SPSS program version 25. This study used multiple linear regression analysis. The result of this study shows that liquidity has a negative but insignificant influence on firm performance, leverage has a negative and significant influence on firm performance, firm size has a positive and significant influence on firm performance, and institutional ownership has a positive but insignificant influence on firm performance.